PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS PADA MATA PELAJARAN IPAS KELAS V SDN NGGARO NANGGA - Hardianti; Syarifuddin, Nur Istiqomah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the impact of a problem-oriented learning approach (Problem-Based Learning/PBL) on students' critical thinking skills during science lessons in grade V of SDN Nggaro Nangga. The basis of this study stems from the low level of students' critical thinking skills who tend to still rely on lecture and memorization methods. In this study, a quantitative method was applied with an experimental design using a single-group pretest-posttest. The total sample in this study involved 18 students. The instrument used included essay exam questions based on five critical thinking indicators. Data analysis was carried out through a Paired Sample t-Test after conducting validity, reliability, normality, and homogeneity tests. The results of this study showed that there was a striking growth in the average pretest score which increased from 55.6 to 86.1 in the posttest, with a t-value reaching 14.92 and a significance of 0.000 which means less than 0.05. The normality and homogeneity tests also stated that the data distribution was normal and homogeneous. Therefore, the PBL model has been shown to be successful in improving students' critical thinking competencies and can be used as an alternative strategy in science learning based on the Independent Curriculum.